PENINGKATAN KETERAMPILAN PRESENTASI SISWA MTS MAMBAUL ‘ULUM JETAK MELALUI PELATIHAN PUBLIC SPEAKING - Yukhsan Wakhyudi, Yukhsan Wakhyudi; Cintya Nurika Irma; Siti Murniasih; Titi Kurniati (PT. Karya Inovatif Nusantara, 2024)
This activity aims to improve the presentation skills of MTs Mambaul 'Ulum Jetak students. Activities are carried out using socialization methods and face-to-face public speaking training by applying theoretical and practical learning. The approach is carried out by means of interviews to look for problems then followed by training activities as an implementation of problem solutions. Problems are obtained and discussed during socialization and problem solving during training sessions. The results of the activity showed that MTs Mambaul 'ulum Jetak students were able to improve their communication skills in presentation activities in class so that this could also support learning activities